2013
DOI: 10.5194/acp-13-10645-2013
|View full text |Cite
|
Sign up to set email alerts
|

Combined SAGE II–GOMOS ozone profile data set for 1984–2011 and trend analysis of the vertical distribution of ozone

Abstract: Abstract.We have studied data from two satellite occultation instruments in order to generate a high vertical resolution homogeneous ozone time series of 26 yr. The Stratospheric Aerosol and Gas Experiment (SAGE) II solar occultation instrument and the Global Ozone Monitoring by Occultation of Stars (GOMOS) instrument measured ozone profiles in the stratosphere and mesosphere from 1984-2005 and 2002-2012, respectively. Global coverage, good vertical resolution, and the self-calibrating measurement method make… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
132
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(171 citation statements)
references
References 35 publications
37
132
2
Order By: Relevance
“…The SSD near the stratopause is quantitatively consistent with the HALOE result of Brühl et al (1996), although they only analyzed two latitude bands at around 18 • N and 18 • S. SAGE II (red solid curve) shows a similar result to HALOE and ACE-FTS, at least qualitatively, but the SSD in the upper stratosphere is approximately twice as large as those resulting from the other data sets. The SAGE II results are essentially consistent with the results of McLinden et al (2009) and Kyrölä et al (2013), although the latter may be partially contaminated by seasonal/interannual ozone variations (see Sect. 3).…”
Section: T Sakazaki Et Al: Sunset-sunrise Difference In Solar Occulsupporting
confidence: 80%
See 4 more Smart Citations
“…The SSD near the stratopause is quantitatively consistent with the HALOE result of Brühl et al (1996), although they only analyzed two latitude bands at around 18 • N and 18 • S. SAGE II (red solid curve) shows a similar result to HALOE and ACE-FTS, at least qualitatively, but the SSD in the upper stratosphere is approximately twice as large as those resulting from the other data sets. The SAGE II results are essentially consistent with the results of McLinden et al (2009) and Kyrölä et al (2013), although the latter may be partially contaminated by seasonal/interannual ozone variations (see Sect. 3).…”
Section: T Sakazaki Et Al: Sunset-sunrise Difference In Solar Occulsupporting
confidence: 80%
“…We see that the SR and SS profiles are not distributed evenly; e.g., there are no SR (SS) profiles from November to January (May to July) between 2001 and 2005 for SAGE II. This indicates that if the SSD is calculated by simply averaging all SR and SS profiles for a certain period (e.g., Kyrölä et al, 2013), it could be significantly contaminated by seasonal/interannual variations in ozone concentrations. In fact, Kyrölä et al (2013) reported that the SSD profile for 2001-2005 was considerably different to those recorded in the other periods (1985-1990, 1991-1995, and 1996-2000); we attribute this to contamination caused by uneven sampling during this period.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 3 more Smart Citations